THE POLICY OF "CLEANING" THE PARTY RANKS OF THE BOLSHEVIKS IN UZBEKISTAN AND ITS CONSEQUENCES - Oybek Rashidov (American Journals Publishing, 2024)
The article examines the policy of "cleansing" the party ranks of the Bolsheviks during the Soviet rule in Uzbekistan and its consequences. The author explained that during the period of Soviet rule, the Center distrusted the activities of national political leaders, unjustified interference in their work, and the fact that they were under strong control.
Keywords: Bolshevik, Soviet, communist, ideological struggle, national politics, nationalism, cleansing of party ranks, totalitarian rule.